A influência dos conceitos evolucionistas nos primeiros trabalhos de Aurélio Quintanilha (1919-1935) - Fonseca, Pedro (2013)
Estuda-se a influência dos conceitos evolucionistas nos primeiros trabalhos de Aurélio Quintanilha (1919-1935)